Formation of photocatalytic plasma electrolytic oxidation coatings on magnesium alloy by incorporation of TiO2 particles - Lu, Xiaopeng
Photocatalytically active plasma electrolytic oxidation coatings on AM50 Mg alloy are reported in the present work. The photocatalytic activity was achieved via introduction of anatase (TiO2 particles) to the treatment bath. The photocatalytic performance of the coating was evaluated by measuring the degradation rate of aqueous methylene blue solution and was primarily related to the anatase content on the coating surface. Lower treatment voltage and a higher amount of particles in the electrolyte can be used to incorporate more anatase into the layer and generate superior photocatalytic coatings. The tailored and functionalized surface provides new functionality for magnesium alloys. (C) 2016 Elsevier B.V. All rights reserved.